ASSESSMENT OF KNOWLEDGE, ATTITUDE, AND PRACTICE OF HEALTH CARE PROFESSIONALS REGARDING COVID-19 VIRUS - Sharif, Bayan Omar; Mohammad, Sara Noori; Ali, Zhino Raouf; Abbas, Varin Tofiq; Ezadin, Shilan Habib; Latif, Avin; Hakim, Kazhal (Journal of Sulaimani Medical College, 2022)
Background COVID-19 is a highly expanding pandemic caused by a novel human coronavirus; it can be transmitted from person to person by close contact via respiratory secretions in coughs or sneezes or by touching viruscontaminated surfaces or objects. So, inadequate knowledge between information and practice and incorrect attitudes among health care professionals can directly influence practical issues and lead to delayed diagnosis, poor infection control practice, and much more spread of disease. Objectives The main aim of this study was to assess health care providers regarding knowledge, attitude, and practice regarding the COVID19 outbreak in two special hospitals for Corona disease in Sulaimani City-Kurdistan region of Iraq, which are (Shahid Aso Hospital and Shahid Hemin hospital) from the period of Jun 26 up to14th of September 2021. Methods In a quantitative design, a descriptive study (non-probability purposive sample) of (127 male and female nurses and physicians), data collection of the study instrument was constructed of a total (of 57) items. The instrument’s content validity was determined through a panel of (7) experts. Data were collected through interview techniques, then organized and coded into computer files. Statistical approaches were used for data analysis by (SPSS version 25). Results Fifty-one percent (51%) of the sample was between the ages of 20 and 30. (63.8 %, 58.3 %, 59.1 %, 61.4 %) were married female government employees who had graduated from the institute of nursing. They most of them were nurses (96.1%). Nearly half of them had (1-5) years of experience. (52%) of them were trained. Only (24% and 13%) of them had a high level of knowledge and practice during their duty, respectively. Nevertheless, the result was significant with the level of education, position, and source of information on the COVID19 virus at a p-value less than 0.05. Conclusion The health care professionals had not enough knowledge to practice their duty. So, the researchers recommended focusing on more training courses regarding the COVID19 virus and guidelines of infection control by the ministry of health/infection control department to develop their knowledge and practice.
Keywords: Knowledge; attitude; practice; Nurses; physicians; COVID19 virus